Established or outsider? Autoethnographic notes on the inclusion of a beginner practitioner in a karate academy in the Western Cariri region of the state of Ceará, Brazil (Agora for Physical Education and Sport, 2025)
From an autoethnography based on participant observation, field diary and the lived experience of social actors, the aim of this work was to present the strangeness and approximations resulting from the inclusion of a beginner practitioner in a karate academy in the Western Cariri region of the state of Ceará, Brazil. The identities of karate practitioners are constructed by specific sociocultural dispositions that direct participants to have cohesion among themselves; in this context, traditional sociocultural aspects of karate are fundamental for the differentiation of these participants in relation to people who practice other martial arts.
Keywords: Autoethnography; karate; culture; martial arts; ethnography